Irony And Sarcasm Detection On Public Figure Speech - Ari Tantra Zuhri; Wahyudin Sagala, Rakhmat (Berpusi Publishing, 2022)
This study discusses the detection of sarcasm found in several speeches. The objectivity of this study is the utterances of Megawati Soekarnoputri and Sukmawati Soekarnoputri speech. The data source for this study is four video samples as primary data and three printed text as secondary data. In this study, seven types of sarcasm from Mike Lamb are used as the foundation for the objective resolution of this study. This study was carried out by cross-checking the analysis, which resulted in sarcasm that is no longer a detection but a solid sarcasm. The method used in this study is a literature review and video-based analysis that analysed seven types of sarcasm by Mike Lamb: self-deprecating, brooding, deadpan, polite, obnoxious, manic, and raging sarcasm. The results got from this study are that the speakers detected 3 of 7 types of sarcasm, referring to Mike Lamb's theory of sarcasm.